2018
DOI: 10.3390/w10091130
|View full text |Cite
|
Sign up to set email alerts
|

Flood Routing in River Reaches Using a Three-Parameter Muskingum Model Coupled with an Improved Bat Algorithm

Abstract: Design of hydraulic structures, flood warning systems, evacuation measures, and traffic management require river flood routing. A common hydrologic method of flood routing is the Muskingum method. The present study attempted to develop a three-parameter Muskingum model considering lateral flow for flood routing, coupling with a new optimization algorithm namely, Improved Bat Algorithm (IBA). The major function of the IBA is to optimize the estimated value of the three-parameters associated with the Muskingum m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 44 publications
(102 reference statements)
0
27
0
1
Order By: Relevance
“…where , and , represent the observed and simulated values, respectively. GA is a method for solving engineering optimization problems that is based on natural selection, the process that drives biological evolution [55][56][57]. The genetic algorithm repeatedly modifies a population of individual solutions.…”
Section: Genetic Algorithm Mehtodmentioning
confidence: 99%
“…where , and , represent the observed and simulated values, respectively. GA is a method for solving engineering optimization problems that is based on natural selection, the process that drives biological evolution [55][56][57]. The genetic algorithm repeatedly modifies a population of individual solutions.…”
Section: Genetic Algorithm Mehtodmentioning
confidence: 99%
“…Improving the Muskingum Routing method using various optimization methods such as hybrid bat-swarm algorithm [9], improved bat algorithm [10], and Wolf Pack Algorithm [11], or combined with a particle filter-based assimilation model [12] for streamflow forecasts; 5.…”
mentioning
confidence: 99%
“…The Bat algorithm is known to be an effective tool for optimization problems. Previous research has shown that it is highly capable of dealing with different issues such as water resource management, energy generation and nonlinear mathematical functions [32,33]. The bats can differentiate the obstacles from food based on sound.…”
Section: Bat Algorithm (Ba)mentioning
confidence: 99%
“…In fact, they generate a loud sound and then receive sound echoes at a specific frequency. Three main assumptions can be made for the BA [33]:…”
Section: Bat Algorithm (Ba)mentioning
confidence: 99%